Electrolyte and secondary battery
The electrolyte solution with fluoroethylene carbonate and lithium difluorobis(oxalate)phosphate forms a robust SEI film, addressing the degradation issues in lithium-ion batteries, enhancing high temperature performance and reducing impedance growth.
Patent Information
- Application Number
- CN202411091343.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-08-09
AI Technical Summary
Existing lithium-ion batteries face challenges in maintaining high temperature cycle performance, high temperature storage performance, and high impedance growth rates, primarily due to the degradation of the solid electrolyte interface (SEI) film during volume changes of the negative electrode.
An electrolyte solution comprising fluoroethylene carbonate and lithium difluorobis(oxalate)phosphate forms a solid electrolyte interface film with high mechanical strength, stability, and ion conductivity, reducing SEI film damage and side reactions, and incorporating additional additives like vinylene carbonate and lithium bis(oxalatoborate) for improved stability at both electrodes.
The solution significantly enhances high temperature cycle and storage performance while reducing impedance growth rates by forming a robust SEI film that withstands volume changes and minimizes direct contact reactions, thereby improving the battery's overall performance.
Smart Images

Figure CN118630316B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to an electrolyte and a secondary battery. Background Art
[0002] Secondary batteries, such as lithium-ion batteries, are widely used in smart phones, wearable devices, consumer drones, electric vehicles and other fields due to their advantages such as high energy density, long cycle life and no memory effect. With the widespread application of lithium-ion batteries in the above fields, the market has continuously increased the energy density of lithium-ion batteries, and at the same time requires them to have good high-temperature storage performance, high-temperature cycle performance and low impedance growth rate.
[0003] As the conductive carrier of ions between the positive and negative electrodes of lithium-ion batteries, the electrolyte is critical to the performance of lithium-ion batteries. Therefore, it is urgent to develop more comprehensive electrolytes to improve the high cycle performance, high temperature storage performance and reduce the impedance growth rate of lithium-ion batteries. Summary of the invention
[0004] The purpose of this application is to provide an electrolyte and a secondary battery to improve the high temperature cycle performance and high temperature storage performance of the secondary battery and reduce the impedance growth rate. The specific technical solution is as follows:
[0005] The first aspect of the present application provides an electrolyte solution, which includes a solvent, an electrolyte and an additive, wherein the additive includes a compound represented by Formula 1, fluoroethylene carbonate and lithium difluorobis(oxalate)phosphate;
[0006] ,
[0007] wherein n is 0 or 1, A is selected from methylene or O, X is selected from sulfonyl or carbonyl, R1 and R2 are each independently selected from H, , and One of, and R1 and R2 are not selected from H at the same time, and at least one sulfur atom is contained in X, R1 and R2. The electrolyte includes the compound shown in Formula 1 within the scope of the present application, fluoroethylene carbonate and lithium difluorobis(oxalate)phosphate, which work together to form a solid electrolyte interface film (SEI film) with high mechanical strength, good stability, high ion conductivity and toughness at the negative electrode interface, effectively reducing the risk of SEI film damage caused by the volume change of the negative electrode sheet during the cycle of the secondary battery, reducing the side reactions caused by direct contact between the electrode material and the electrolyte, reducing the risk of lithium precipitation on the negative electrode surface, improving the high temperature cycle performance and high temperature storage performance of the secondary battery and reducing the impedance growth rate.
[0008] In some embodiments of the present application, based on the mass of the electrolyte, the mass percentage of the compound represented by Formula 1 is M AThe mass percentage of fluoroethylene carbonate is M B The mass percentage of lithium difluorobis(oxalate)phosphate is M C , meet: 0.5%≤M A ≤7%, 5%≤M B ≤20%, 0.1%≤M C ≤1%. The electrolyte includes the compound shown in Formula 1, fluoroethylene carbonate and lithium difluorobisoxalate phosphate within the scope of the present application, and the contents of the compound shown in Formula 1, fluoroethylene carbonate and lithium difluorobisoxalate phosphate are regulated within the scope of the present application. The three act synergistically, which is conducive to further forming a solid electrolyte interface film (SEI film) with high mechanical strength, good stability, high ion conductivity and toughness at the negative electrode interface, effectively reducing the risk of SEI film damage caused by the volume change of the negative electrode sheet during the cycle of the secondary battery, reducing the side reactions caused by the direct contact between the electrode material and the electrolyte, reducing the risk of lithium precipitation on the negative electrode surface, and further improving the high temperature cycle performance and high temperature storage performance of the secondary battery and reducing the impedance growth rate.
[0009] In some embodiments of the present application, the compound represented by Formula 1 is selected from the compound represented by Formula 2:
[0010] ,
[0011] Among them, X, R1 and R2 contain 1 or 2 sulfur atoms.
[0012] In some embodiments of the present application, the compound represented by Formula 1 is selected from at least one of the following compounds:
[0013] .
[0014] In some embodiments of the present application, the electrolyte satisfies at least one of the following conditions: (1) 1%≤M A ≤5%; (2) 10%≤M B ≤15%; (3) 0.5%≤M C ≤1%. The electrolyte satisfies at least one of (1) to (3), which can further improve the performance of the SEI film, thereby further improving the high-temperature cycle performance and high-temperature storage performance of the secondary battery and reducing the impedance growth rate.
[0015] In some embodiments of the present application, the additive further includes other additives, the other additives are selected from at least one of vinylene carbonate and lithium bis(oxalatoborate); based on the mass of the electrolyte, the mass percentage of the other additives is M D , 0.3%≤M DThe electrolyte includes other additives within the above range and the mass percentage of other additives is regulated within the scope of the present application, which is conducive to forming a stable interface film at the positive electrode and the negative electrode, and further improving the high temperature cycle performance of the secondary battery.
[0016] In some embodiments of the present application, the electrolyte is selected from at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalatoborate) and lithium difluorooxalatoborate, and the mass percentage of the electrolyte is M based on the mass of the electrolyte. E , 12%≤M E ≤18%. The electrolyte includes the electrolyte within the above range, and the mass percentage of the electrolyte is regulated within the scope of the present application, so that the electrolyte has higher ionic conductivity and good electrochemical stability, and can further improve the high temperature cycle performance and high temperature storage performance of the secondary battery.
[0017] In some embodiments of the present application, the solvent is selected from at least two of propylene carbonate, ethyl methyl carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, cyclopentane, methyl formate, ethyl formate, propyl formate, butyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate and butyl butyrate, and the mass percentage of the solvent is M based on the mass of the electrolyte. F , 55%≤M F The electrolyte includes a solvent within the above range, and the mass percentage of the solvent is regulated within the scope of the present application, so that the electrolyte has a suitable viscosity, a high ionic conductivity and good electrochemical stability, which can further improve the high temperature cycle performance and high temperature storage performance of the secondary battery.
[0018] The second aspect of the present application provides a secondary battery, which includes a negative electrode plate, a positive electrode plate, a separator and the electrolyte provided in the first aspect of the present application.
[0019] In some embodiments of the present application, the negative electrode sheet includes a negative electrode material layer, the negative electrode material layer includes a negative electrode active material, and the mass percentage of silicon element is M based on the mass of the negative electrode active material. Si After the secondary battery is formed, based on the mass of the electrolyte, the mass percentage of the compound shown in Formula 1 is M a The mass percentage of fluoroethylene carbonate is M b The mass percentage of lithium difluorobis(oxalate)phosphate is M cThe formation condition is to place the secondary battery in an environment of 40°C to 50°C, charge it at a constant current, charge the secondary battery to a charge state of 70% to 100%, and the constant current is 0.05C to 0.15C; the secondary battery satisfies the relationship I: 15≤[15×(M A +M B ) / (M a +M b )+10×M C × (M C -M c )] / (1.5+M Si )≤234, where the filling coefficient of the secondary battery is 1.5+M Si , the unit is g / Ah. When the secondary battery satisfies the above relationship I, the energy density of the secondary battery can be improved, and the high temperature cycle performance and high temperature storage performance of the secondary battery can be taken into account while reducing the impedance growth rate.
[0020] In some embodiments of the present application, 10%≤M Si ≤30%. By adjusting M si The value of is within the scope of the present application, which is beneficial to improving the energy density of the secondary battery, taking into account the high-temperature cycle performance and high-temperature storage performance of the secondary battery and reducing the impedance growth rate.
[0021] In some embodiments of the present application, the secondary battery satisfies at least one of the following conditions: (1) 0.01%≤M a ≤1.81%; (2) 0.24%≤M b ≤7.23%; (3) 0%≤M c ≤0.33%. After the secondary battery is formed, after the compound shown in Formula 1, FEC or LiODFP in the electrolyte is converted into a SEI film, the remaining compound shown in Formula 1 is conducive to weakening the interaction between lithium ions and solvent molecules, making lithium ions easy to desolvate and improving the reversible deintercalation of lithium ions in the negative electrode; the remaining FEC is conducive to repairing the damaged SEI film; the remaining LiODFP can further improve the ionic conductivity of the electrolyte. Therefore, when the secondary battery meets at least one of the above conditions, the high-temperature cycle performance and high-temperature storage performance of the secondary battery can be further improved and the impedance growth rate can be reduced.
[0022] In some embodiments of the present application, the secondary battery satisfies the relation II: 16≤[15× (M A +M B ) / (M a +M b )+10×M C ×(M C -M c )] / (1.5+MSi )≤83.3. When the secondary battery satisfies the above relationship II, the energy density of the secondary battery can be improved, while taking into account the high temperature cycle performance and high temperature storage performance of the secondary battery and reducing the impedance growth rate.
[0023] In some embodiments of the present application, the secondary battery satisfies the relationship III: 16≤[15× (M A +M B ) / (M a +M b )+10×M C × (M C -M c )] / (1.5+M Si )≤33. When the secondary battery satisfies the above relationship III, the energy density of the secondary battery can be further improved, while taking into account the high temperature cycle performance and high temperature storage performance of the secondary battery and reducing the impedance growth rate.
[0024] Beneficial effects of this application:
[0025] The present application provides an electrolyte and a secondary battery. The electrolyte includes a solvent, an electrolyte and an additive. The additive includes a compound shown in Formula 1, fluoroethylene carbonate and lithium difluorobis(oxalyl)phosphate. The synergistic effect of the three is conducive to forming a solid electrolyte interface film with high mechanical strength, good stability, high ion conductivity and toughness at the negative electrode interface, which can significantly improve the high-temperature cycle performance and high-temperature storage performance of the secondary battery and reduce the impedance growth rate.
[0026] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0028] It should be noted that in the specific implementation of the present application, lithium-ion batteries are used as an example of secondary batteries to explain the present application, but the secondary batteries of the present application are not limited to lithium-ion batteries. The specific technical solutions are as follows:
[0029] The first aspect of the present application provides an electrolyte solution, which includes a solvent, an electrolyte and an additive, wherein the additive includes a compound represented by Formula 1, fluoroethylene carbonate and lithium difluorobis(oxalate)phosphate;
[0030] ,
[0031] wherein n is 0 or 1, A is selected from methylene or O, X is selected from sulfonyl or carbonyl, R1 and R2 are each independently selected from H, , and One of, and R1 and R2 are not selected from H at the same time, and at least one sulfur atom is contained in X, R1 and R2. The electrolyte includes the compound shown in Formula 1 within the scope of the present application, fluoroethylene carbonate and lithium difluorobis(oxalate)phosphate, and the three act synergistically to form a solid electrolyte interface film (SEI film) with high mechanical strength, good stability, high ionic conductivity and toughness at the negative electrode interface, effectively reducing the risk of SEI film damage caused by the volume change of the negative electrode sheet during the cycle of the secondary battery, reducing the side reactions caused by the direct contact between the electrode material and the electrolyte, reducing the risk of lithium precipitation on the negative electrode surface, improving the high temperature cycle performance and high temperature storage performance of the secondary battery and reducing the impedance growth rate.
[0032] The inventors have found that during the first charging process of the secondary battery, the compound shown in Formula 1 of the present application will preferentially decompose at a low potential, so that the generated solid electrolyte interface film (SEI film) is rich in inorganic components such as Li2SO4 and Li2CO3, and active metal ions (such as Li + ) has many diffusion sites, which is beneficial to reducing the membrane impedance of the negative electrode interface, and the compound represented by formula 1 which is rich in double bonds is easy to undergo reduction reaction at the negative electrode and polymerize to form an insoluble organic film. The insoluble organic film can act as an elastic component in the SEI film, making the SEI film tough to cope with the volume expansion of the negative electrode. However, when the volume of the negative electrode expands greatly, the SEI film is not tough enough and will still break. The negative electrode active material and the electrolyte are in direct contact and side reactions occur, which affect the high-temperature cycle performance and high-temperature storage performance of the secondary battery and increase the impedance of the secondary battery. To address this problem, the present application further introduces fluoroethylene carbonate (FEC) and lithium difluorobis(oxalate) phosphate (LiODFP) into the electrolyte. FEC decomposes at the negative electrode interface to provide a large number of double-bond and triple-bond monomers, which polymerize to form a polymer film with a low Young's modulus and excellent toughness, further improving the toughness of the SEI film, effectively inhibiting the damage of the SEI film caused by the volume change of the negative electrode, reducing the side reactions caused by the direct contact between the negative electrode active material and the electrolyte, further improving the high-temperature cycle performance and high-temperature storage performance of the secondary battery and reducing the impedance growth rate. The introduction of LiODFP provides the SEI film with abundant Li3PO4 and LiF, which is beneficial to provide more Li + The space charge layer formed between the vacancies and the defects on the negative electrode interface will further enhance the ionic conductivity of the negative electrode interface, which is beneficial to the transmission of lithium ions, reduces the risk of lithium deposition on the negative electrode surface, and further improves the high temperature cycle performance and safety performance of the secondary battery.
[0033] In some embodiments of the present application, based on the mass of the electrolyte, the mass percentage of the compound represented by Formula 1 is M A The mass percentage of fluoroethylene carbonate is M B The mass percentage of lithium difluorobis(oxalate)phosphate is M C , meet: 0.5%≤M A ≤7%, 5%≤M B ≤20%, 0.1%≤M C ≤1%, optionally, 1%≤M A ≤3%,10%≤M B ≤15%, 0.5%≤M C ≤1%. For example, M A The value of can be 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5%, 5.2%, 5.5%, 5.8%, 6%, 6.2%, 6.5%, 6.8%, 7%, or a range consisting of any two values thereof, M B The value of can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, or a range consisting of any two values thereof. C The value of can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or a range consisting of any two of them. A If the value is too small, for example, M A Less than 0.5%, the generated SEI film contains less inorganic components such as Li2SO4 and Li2CO3, and active metal ions (such as Li + ) There are fewer diffusion sites, which is not conducive to reducing the impedance growth rate; when M A When the value of is too large, for example, greater than 7%, the SEI film will be too thick and the capacity loss of the secondary battery will be obvious. B If the value is too small, for example, M B When M is less than 5%, the SEI film is not tough enough. When the volume of the negative electrode expands greatly, the SEI film is easy to rupture and cannot be repaired in time. The negative electrode active material and the electrolyte are in direct contact and side reactions occur, which affects the high-temperature cycle performance and high-temperature storage performance of the secondary battery and increases the impedance of the secondary battery. B When the value is too large, for example, greater than 20%, the viscosity of the electrolyte is high, which is not conducive to the active metal ions (such as Li +) transmission, and the residual FEC in the electrolyte is easy to decompose and produce gas at high temperature, resulting in serious volume expansion of the secondary battery, which seriously affects the high-temperature cycle performance and high-temperature storage performance of the secondary battery and increases the impedance of the secondary battery. C If the value is too small, for example, M C When M is less than 0.1%, the formed SEI film has less inorganic components, the SEI film strength is reduced, and when the negative electrode volume expands, the SEI film is easy to rupture, and the negative electrode active material and the electrolyte are in direct contact with each other to cause side reactions, which affects the high-temperature cycle performance and high-temperature storage performance of the secondary battery and increases the impedance of the secondary battery. C When the value is too large, for example, greater than 1%, too much LiODFP decomposes in the electrolyte, the -F in LiODFP breaks, and reacts with trace water in the electrolyte to generate HF, which will destroy the interface film of the positive and negative electrodes, affecting the high temperature cycle performance and high temperature storage performance of the secondary battery. The electrolyte of the present application includes the compound shown in Formula 1, FEC and LiODFP at the same time, and the mass percentage of the compound shown in Formula 1, FEC and LiODFP is regulated within the scope of the present application. The synergistic effect of the three is conducive to the formation of a solid electrolyte interface film with high mechanical strength, good stability, high ionic conductivity and toughness at the negative electrode interface, which can significantly improve the high temperature cycle performance and high temperature storage performance of the secondary battery, and reduce the impedance growth rate.
[0034] In some embodiments of the present application, the compound represented by Formula 1 is selected from the compound represented by Formula 2:
[0035] ,
[0036] Wherein, X, R1 and R2 contain 1 or 2 sulfur atoms. The compound represented by Formula 1 is selected from the compound represented by Formula 2, which is beneficial to improving the mechanical strength, stability and toughness of the SEI film, further improving the high temperature cycle performance and high temperature storage performance of the secondary battery, and reducing the impedance growth rate.
[0037] In some embodiments of the present application, the compound represented by Formula 1 is selected from at least one of the following compounds:
[0038] .
[0039] The electrolyte includes the compound represented by Formula 1 within the above range, which is beneficial to improving the mechanical strength, stability and toughness of the SEI film, can further improve the high-temperature cycle performance and high-temperature storage performance of the secondary battery, and reduce the impedance growth rate.
[0040] In some embodiments of the present application, the additive further includes other additives, and the other additives are selected from at least one of vinylene carbonate (VC) and lithium bis(oxalatoborate) (LiBOB); based on the mass of the electrolyte, the mass percentage of the other additives is M D , 0.3%≤M D ≤5%. For example, M D The value of can be 0.3%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5% or a range consisting of any two of the values. The electrolyte includes other additives within the above range and regulates the mass percentage of other additives within the scope of this application, which is conducive to forming a stable interface film at the positive electrode and the negative electrode, and further improving the high temperature cycle performance of the secondary battery.
[0041] In some embodiments of the present application, the electrolyte is selected from at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalatoborate) and lithium difluorooxalatoborate, and the mass percentage of the electrolyte is M based on the mass of the electrolyte. E , 12%≤M E ≤18%; for example, M E The value of can be 12%, 13%, 14%, 15%, 16%, 17%, 18% or a range consisting of any two of the values. The electrolyte includes an electrolyte within the above range, and the mass percentage of the electrolyte is regulated within the scope of the present application, so that the electrolyte has a higher ionic conductivity and good electrochemical stability, which can further improve the high temperature cycle performance and high temperature storage performance of the secondary battery.
[0042] In some embodiments of the present application, the solvent is selected from at least two of propylene carbonate, ethyl methyl carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, cyclopentane, methyl formate, ethyl formate, propyl formate, butyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate and butyl butyrate, and the mass percentage of the solvent is M based on the mass of the electrolyte. F , 55%≤M F ≤80%; for example, M FThe value of can be 55%, 58%, 60%, 62%, 65%, 68%, 70%, 72%, 75%, 78%, 80% or a range consisting of any two of the values. The electrolyte includes a solvent within the above range, and the mass percentage of the solvent is regulated within the scope of the present application, so that the electrolyte has a suitable viscosity, a high ionic conductivity and good electrochemical stability, which can further improve the high temperature cycle performance and high temperature storage performance of the secondary battery.
[0043] The second aspect of the present application provides a secondary battery, which includes a negative electrode plate, a positive electrode plate, a separator and the electrolyte provided in the first aspect of the present application.
[0044] In some embodiments of the present application, the negative electrode sheet includes a negative electrode material layer, the negative electrode material layer includes a negative electrode active material, and the mass percentage of silicon element is M based on the mass of the negative electrode active material. Si After the secondary battery is formed, based on the mass of the electrolyte, the mass percentage of the compound shown in Formula 1 is M a The mass percentage of fluoroethylene carbonate is M b The mass percentage of lithium difluorobis(oxalate)phosphate is M c The formation conditions are to place the secondary battery in an environment of 40°C to 50°C, charge it at a constant current, charge the secondary battery to a charge state of 70% to 100%, and the constant current is 0.05C to 0.15C; the secondary battery satisfies the relationship I: 15≤[15× (M A +M B ) / (M a +M b )+10×M C × (M C -M c )] / (1.5+M Si )≤234, where the filling coefficient of the secondary battery is 1.5+M Si , in units of g / Ah; Optionally, the secondary battery satisfies the relationship II: 16≤[15× (M A +M B ) / (M a +M b )+10×M C ×(M C -M c )] / (1.5+M Si )≤83.3; Further optionally, the secondary battery satisfies the relation III: 16≤[15× (M A +M B ) / (M a +M b )+10×M C × (MC -M c )] / (1.5+M Si )≤33. For example, the value of relational formula I can be 15, 16, 17, 18, 19, 20, 21, 22, 24, 25, 26, 27, 30, 33, 35, 40, 50, 60, 70, 80, 83.3, 90, 100, 120, 140, 160, 180, 200, 220, 230, 234 or a range consisting of any two of the values. It should be noted that the unit of the injection coefficient can also be mg / mAh.
[0045] In the present application, the silicon element in the negative electrode active material is derived from a silicon-based material, and the silicon-based material may include but is not limited to at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites, or silicon alloys. The negative electrode active material also includes a carbon-based material, and the carbon-based material may include but is not limited to at least one of artificial graphite, natural graphite, soft carbon, hard carbon, or mesophase microcarbon beads.
[0046] Silicon-based materials have a high theoretical capacity, which is beneficial to improving the energy density of secondary batteries. However, during the charging and discharging process of the secondary battery, as lithium ions are embedded and extracted, the silicon-based materials will undergo a volume expansion of 120% to 300%. The use of the electrolyte provided in the present application is conducive to forming a solid electrolyte interface film with high mechanical strength, good stability, high ionic conductivity and toughness at the negative electrode interface, which can effectively inhibit the rupture of the SEI film caused by the expansion of the silicon-based material and reduce the side reactions caused by the direct contact between the negative electrode active material and the electrolyte; and after the secondary battery is formed, the compound shown in formula 1, FEC or LiODFP in the electrolyte is converted into a SEI film, and the remaining compound shown in formula 1 is conducive to weakening the interaction between lithium ions and solvent molecules, making lithium ions easy to desolvate and improving the reversible embedding and extraction of lithium ions at the negative electrode; the remaining FEC is conducive to repairing the damaged SEI film; and the remaining LiODFP can further improve the ionic conductivity of the electrolyte. When the secondary battery satisfies the above relationship, the energy density of the secondary battery can be improved, while taking into account the high-temperature cycle performance and high-temperature storage performance of the secondary battery and reducing the impedance growth rate.
[0047] In some embodiments of the present application, 10%≤M Si ≤30%, for example, M si The value of can be 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30% or a range consisting of any two of these values. si The value of is within the scope of the present application, which is beneficial to improving the energy density of the secondary battery, taking into account the high-temperature cycle performance and high-temperature storage performance of the secondary battery and reducing the impedance growth rate.
[0048] In some embodiments of the present application, 0.01%≤M a ≤1.81%, for example, M a The value of can be 0.01%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.81%, or a range consisting of any two of them. a The value of is within the scope of the present application, which is beneficial for the compound represented by Formula 1 to weaken the interaction between lithium ions and solvent molecules, making lithium ions easy to desolvate, improving the reversible deintercalation of lithium ions at the negative electrode, further improving the high temperature cycle performance and high temperature storage performance of the secondary battery and reducing the impedance growth rate.
[0049] In some embodiments of the present application, 0.24%≤M b ≤7.23%, for example, M b The value of can be 0.24%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.23% or a range consisting of any two of them. b The value of is within the scope of the present application, which is beneficial to repairing the damaged SEI film, further improving the high-temperature cycle performance and high-temperature storage performance of the secondary battery and reducing the impedance growth rate.
[0050] In some embodiments of the present application, 0%≤M c ≤0.33%, for example, M c The value of can be 0%, 0.05%, 0.1%, 0.12%, 0.15%, 0.18%, 0.2%, 0.22%, 0.25%, 0.28%, 0.3%, 0.33%, or a range consisting of any two of these values. c The value of is within the scope of the present application, which is beneficial to further improve the ionic conductivity of the electrolyte, further improve the high-temperature cycle performance and high-temperature storage performance of the secondary battery and reduce the impedance growth rate.
[0051] Usually, when other conditions remain unchanged, M a 、M b 、M c The value of M can be changed by A 、M B 、M C For example, increasing M A The value of M a Increase; decrease M A The value of M a Decrease. Increase M BThe value of M b Increase; decrease M B The value of M b Decrease. Increase M C The value of M c Increase; decrease M C The value of M c When other conditions remain unchanged, M a 、M b 、M c The value of M can also be changed by Si For example, increasing M Si The value of M a 、M b 、M c The value of M decreases; Si The value of M a 、M b 、M c Combined with the "M a 、M b 、M c The corresponding M a 、M b 、M c The value of .
[0052] In the present application, the negative electrode plate includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode material layer is disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or it can be disposed on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the negative electrode current collector, or it can be a partial area of the surface of the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved. This application has no special restrictions on the negative electrode current collector, as long as the purpose of this application can be achieved. For example, the negative electrode current collector can be copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel or foam copper, aluminum foil or a composite negative electrode current collector. The composite negative electrode current collector may be a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The material of the polymer material base layer may include but is not limited to at least one of polypropylene (PP), polyethylene terephthalate (PET) or polybutylene terephthalate (PBT), and the material of the metal layer may include but is not limited to at least one of copper, copper alloy, nickel or nickel alloy. The present application has no particular restrictions on the thickness of the negative electrode material layer and the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the single-sided negative electrode material layer is 50μm to 180μm, and the thickness of the negative electrode current collector is 3μm to 10μm.
[0053] The present application does not particularly limit the types of negative electrode conductors and negative electrode binders, as long as the purpose of the present application can be achieved. For example, the negative electrode conductor may include but is not limited to at least one of superconducting carbon black (Super P), acetylene black, Ketjen black, carbon nanotubes, graphene or carbon fibers. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. For example, the negative electrode binder may include but is not limited to at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), sodium carboxymethyl cellulose (CMC), polymethacrylic acid (PMAA) or carboxymethyl chitosan (CMCS).
[0054] In the present application, there is no particular restriction on the method for preparing the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, it can be prepared by the following method: carbon-based materials and silicon-based materials are mixed in a certain proportion, mixed evenly to obtain negative electrode active materials, and then the negative electrode active materials, negative electrode conductive agents, and negative electrode binders are added with deionized water and stirred evenly to obtain a negative electrode slurry with a solid content of 45wt% to 70wt%. The negative electrode slurry is evenly coated on one surface of the negative electrode current collector, and a negative electrode sheet coated with a negative electrode material layer on one side is obtained after drying. Then the above coating steps are repeated on the other surface of the negative electrode current collector, and a negative electrode sheet coated with a negative electrode material layer on both sides is obtained after drying. After coating, the negative electrode sheet is obtained by cold pressing and cutting.
[0055] Generally, when other conditions remain unchanged, the mass percentage of silicon in the negative electrode active material can be regulated by adjusting the ratio of carbon-based materials to silicon-based materials. For example, by increasing the ratio of carbon-based materials to silicon-based materials, the mass percentage of silicon in the negative electrode active material decreases; by decreasing the ratio of carbon-based materials to silicon-based materials, the mass percentage of silicon in the negative electrode active material increases.
[0056] In the present application, the secondary battery includes a positive electrode plate, and the positive electrode plate includes a positive electrode collector and a positive electrode material layer disposed on at least one surface of the positive electrode collector. The above-mentioned "positive electrode material layer disposed on at least one surface of the positive electrode collector" means that the positive electrode material layer can be disposed on one surface of the positive electrode collector along the thickness direction of itself, or on two surfaces of the positive electrode collector along the thickness direction of itself. It should be noted that the "surface" here can be the entire area of the surface of the positive electrode collector, or it can be a partial area of the surface of the positive electrode collector. This application has no special restrictions, as long as the purpose of this application can be achieved. This application has no special restrictions on the positive electrode collector, as long as the purpose of this application can be achieved. For example, the positive electrode collector can be aluminum foil, aluminum alloy foil or a composite positive electrode collector. The composite positive electrode current collector may be a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The material of the polymer material base layer may include but is not limited to at least one of polypropylene (PP), polyethylene terephthalate (PET) or polybutylene terephthalate (PBT), and the material of the metal layer may include but is not limited to at least one of aluminum, aluminum alloy, nickel or nickel alloy. The present application has no particular restrictions on the thickness of the positive electrode material layer and the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the single-sided positive electrode material layer is 50μm to 250μm, and the thickness of the positive electrode current collector is 7μm to 15μm.
[0057] The positive electrode material layer includes a positive electrode active material. The present application has no particular limitation on the positive electrode active material as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to at least one of lithium nickel cobalt manganese oxide (such as NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium iron manganese phosphate or lithium titanate.
[0058] The positive electrode material layer may also include a positive electrode conductor and a positive electrode binder. The present application does not particularly limit the types of the positive electrode conductor and the positive electrode binder, as long as the purpose of the present application can be achieved. For example, the positive electrode conductor may include but is not limited to at least one of superconducting carbon black (Super P), acetylene black, Ketjen black, carbon nanotubes, graphene or carbon fiber. For example, the positive electrode binder may include but is not limited to polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer or fluorine-containing acrylate resin. The present application does not particularly limit the mass ratio of the positive active material, the conductive agent, and the binder in the positive electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.
[0059] In the present application, there is no particular restriction on the method for preparing the positive electrode sheet, as long as the purpose of the present application can be achieved. For example, it can be prepared by the following method: the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder are mixed, N-methylpyrrolidone (NMP) is added and stirred evenly, and a positive electrode slurry with a solid content of 50wt% to 85wt% is obtained. The positive electrode slurry is evenly coated on one surface of the positive electrode collector, and a positive electrode sheet coated with a positive electrode material layer on one side is obtained after drying. Then the above coating steps are repeated on the other surface of the positive electrode collector, and a positive electrode sheet coated with a positive electrode material layer on both sides is obtained after drying. After coating, the positive electrode sheet is obtained by cold pressing and cutting.
[0060] In the present application, the secondary battery also includes a separator. The present application has no particular restrictions on the separator, as long as the purpose of the present application can be achieved. For example, the material of the separator may include but is not limited to at least one of polyethylene (PE), polypropylene (PP), glass fiber, polyester (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), and polyamide (PA). The type of separator may include at least one of a woven membrane, a non-woven fabric, a microporous membrane, a composite membrane, a rolled membrane, or a spun membrane. In the present application, the thickness of the separator is not particularly limited, as long as the purpose of the present application can be achieved. For example, the thickness of the separator may be 4 μm to 20 μm.
[0061] In the present application, the secondary battery also includes a shell for accommodating a positive electrode plate, a separator, a negative electrode plate and an electrolyte, as well as other components known in the field of secondary batteries, and the present application does not limit the above-mentioned other components. The present application has no special restrictions on the shell, and it can be a shell known in the art, as long as the purpose of the present application can be achieved. For example, the shell can be a hard shell or a flexible shell. The material of the hard shell can be metal, and the present application does not limit the type of metal. A metal hard shell known in the art can be used, as long as the purpose of the present application can be achieved. The flexible shell can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.
[0062] The secondary battery of the present application is not particularly limited, and may include any device that generates an electrochemical reaction. In one embodiment of the present application, the secondary battery may include, but is not limited to, a lithium ion secondary battery (lithium ion battery), a sodium ion secondary battery (sodium ion battery), and the like.
[0063] The preparation process of the secondary battery of the present application is well known to those skilled in the art, and there is no particular limitation in the present application. For example, the preparation process of the secondary battery may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a winding structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain a secondary battery. Alternatively, stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire laminated structure with tape to obtain an electrode assembly of a laminated structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain a secondary battery. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the shell as needed to prevent the pressure inside the secondary battery from rising and overcharging and discharging.
[0064] Example
[0065] Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are by mass.
[0066] Test methods and equipment:
[0067] M a 、M b 、M c Test
[0068] The lithium-ion batteries after the formation of the embodiment and the comparative example are disassembled, the electrolyte is collected, and the positive electrode sheet, negative electrode sheet, and diaphragm are centrifuged, and the liquid obtained after the centrifugation is mixed with the above electrolyte to obtain a liquid sample, and the liquid sample is subjected to ion chromatography (IC) testing to measure the type and content of salt compounds such as lithium hexafluorophosphate and lithium difluorobisoxalate phosphate in the electrolyte. The above liquid sample is tested by gas chromatography-mass spectrometry (GC-MS) to measure the mass ratio of the remaining components in the electrolyte, and then combined with the above measured content of lithium hexafluorophosphate and lithium difluorobisoxalate phosphate and other salts to calculate the mass percentage of each component in the electrolyte, thereby obtaining the M in the electrolyte after the formation. a 、M b 、M c The value of .
[0069] High temperature cycle performance test
[0070] The lithium-ion battery was placed in a 45°C constant temperature box for 4 hours, and then charged at a constant current of 1C to a voltage of 4.25V, and then charged at a constant voltage of 4.25V to a current of 0.05C, and then discharged at a constant current of 1C to a voltage of 2.75V, and the initial discharge capacity was recorded as C1. This was a charge and discharge cycle, and the above charge and discharge cycles were repeated for 1200 times, and the discharge capacity after the 1200th cycle was recorded as C2. The charge and discharge cycle test instrument is Xinwei BTS.
[0071] 45℃ capacity retention rate (%) = C2 / C1×100%; The high-temperature cycle performance of lithium-ion batteries is evaluated by the 45℃ capacity retention rate. The larger the capacity retention rate, the better the high-temperature cycle performance of the lithium-ion battery.
[0072] High temperature storage performance test
[0073] Place the lithium-ion battery in a 25℃ constant temperature box and let it stand for 4h. Then charge the lithium-ion battery at a constant current of 1C to a voltage of 4.25V, then charge it at a constant voltage of 4.25V to a current of 0.05C, then discharge it at a constant current of 1C to a voltage of 2.75V, record the initial discharge capacity as Q1, test the initial thickness of the lithium-ion battery D1, then charge the lithium-ion battery at a constant current of 1C to a voltage of 4.25V, then charge it at a constant voltage of 4.25V to a current of 0.05 C, then place the lithium-ion battery in an explosion-proof oven at 60℃. After storage for 30 days, test the battery thermal thickness D2 in the oven. Then take out the lithium-ion battery and cool it to room temperature. At 25℃, discharge the lithium-ion battery at a constant current of 1C to a voltage of 2.75V, and record the discharge capacity at this time as Q2. Then charge the lithium-ion battery at a constant current of 1C to a voltage of 4.25V, and then charge at a constant voltage of 4.25V to a current of 0.05C, and record the charging capacity at this time as Q3.
[0074] Storage thickness expansion rate (%) = (D2-D1) / D1×100%;
[0075] Storage capacity retention rate (%) = Q2 / Q1×100%;
[0076] Storage capacity recovery rate (%) = Q3 / Q1×100%;
[0077] The high-temperature storage performance of lithium-ion batteries is evaluated by the storage thickness expansion rate, storage capacity retention rate and storage capacity recovery rate. The smaller the storage thickness expansion rate and the larger the storage capacity retention rate and storage capacity recovery rate, the better the high-temperature storage performance of the lithium-ion battery.
[0078] DC resistance (DCR) test
[0079] DCR1 test of lithium-ion battery before storage: place the lithium-ion battery in a 25℃ environment, charge it at 1C constant current to a voltage of 4.25V, then charge it at 4.25V constant voltage to a current of 0.05C, leave it for 30min, then discharge it at 1C constant current for 30min (adjust to 50% SOC, SOC refers to the battery's state of charge), record the end voltage as V1, leave it for 1h, then discharge it at 2C constant current for 10s, record the end voltage as V2, and calculate the DCR1 before storage = (V1-V2) / (2C-1C);
[0080] Test of DCR2 after storage of lithium-ion battery: Place the above lithium-ion battery in a 60℃ explosion-proof oven, take it out after 30 days of storage, place the lithium-ion battery in a 25℃ environment, charge it at 1C constant current to a voltage of 4.25V, then charge it at 4.25V constant voltage to a current of 0.05C, leave it for 30min, then discharge it at 1C constant current for 30min (adjust to 50% SOC, SOC refers to the state of charge of the battery), record the end voltage as V3, leave it for 1h, then discharge it at 2C constant current for 10s, record the end voltage as V4, and calculate DCR2 before storage = (V3-V4) / (2C-1C);
[0081] Impedance growth rate (%) = (DCR2-DCR1) / DCR1×100%.
[0082] Example 1-1
[0083] <Preparation of Electrolyte>
[0084] In an inert atmosphere with a water content of less than 0.1 ppm and an oxygen content of less than 1 ppm, ethylene carbonate (EC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 1:1:1 to obtain a basic solvent, and then the electrolyte lithium hexafluorophosphate (LiPF6), the compound shown in formula 1-1, fluoroethylene carbonate (FEC), and lithium difluorobis(oxalate) phosphate (LiODFP) are added to the basic solvent and mixed evenly to obtain an electrolyte. Among them, based on the mass of the electrolyte, the mass percentage of LiPF6 is 15%, the mass percentage of the compound shown in formula 1-1 is 2%, the mass percentage of FEC is 12%, the mass percentage of LiODFP is 0.7%, and the remaining base solvent is 70.3%.
[0085] <Preparation of negative electrode sheet>
[0086] The negative electrode active material artificial graphite, the negative electrode active material single silicon, the conductive agent acetylene black, the binder sodium carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR) were mixed in a mass ratio of 87.3:9.7:1:1:1, and deionized water was added as a solvent to prepare a slurry with a solid content of 49wt%. The negative electrode slurry was obtained after being stirred evenly by a vacuum mixer. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 9μm, and dried at 90°C to obtain a negative electrode sheet with a single-sided coating of a negative electrode material layer. The coating weight of the negative electrode material layer was 8mg / mm 2 Then repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet with a negative electrode material layer on both sides. After drying at 85°C, roll pressing, slitting and welding the tabs, a negative electrode sheet with a specification of 74mm×59mm is obtained for standby use. Among them, the thickness of the single-sided negative electrode material layer is 111μm; based on the mass of the negative electrode active material, the mass percentage of silicon element M Si is 10%.
[0087] <Preparation of positive electrode sheet>
[0088] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), positive electrode conductive agent acetylene black and positive electrode binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 96:2:2, and N-methylpyrrolidone (NMP) was added as a solvent to prepare a slurry with a solid content of 55wt%. The positive electrode slurry was obtained after vacuum stirring. The positive electrode slurry was evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 12μm, and dried at 90°C to obtain a positive electrode sheet with a single-sided coating of a positive electrode material layer. The coating weight of the positive electrode material layer was 17mg / mm 2 Then repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. After drying at 85°C, roll pressing, slitting and welding the tabs, a positive electrode sheet with a specification of 70mm×55mm is obtained for standby use. The thickness of the single-sided positive electrode material layer is 158μm.
[0089] <Preparation of Separator>
[0090] A polyethylene (PE) porous membrane with a thickness of 10 µm (provided by Shenzhen Xingyuan Material Technology Co., Ltd.) was used as the separator.
[0091] <Preparation of lithium-ion batteries>
[0092] The positive electrode sheet, separator and negative electrode sheet prepared above are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and the electrode assembly is wound. The electrode assembly is placed in an aluminum plastic film packaging bag, and the water is removed at 85°C, and the electrolyte prepared above is injected, and the injection coefficient is 1.6g / Ah. After vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained. Among them, the standing time is 48 hours, the forming current is 0.1C, the upper limit voltage of the forming is 4.25V, and the forming temperature is 45°C.
[0093] Example 1-2 to Example 1-15
[0094] Except that the relevant parameters in <Preparation of Electrolyte> are adjusted according to Table 1, the rest are the same as Example 1-1. A 、M B 、M C When the value of changes, the mass percentage of the solvent M F As a result, the mass percentage of the electrolyte M E constant.
[0095] Example 1-16 to Example 1-30
[0096] Except that in the preparation of the negative electrode sheet, the negative electrode active material artificial graphite, the negative electrode active material single substance silicon, the conductive agent acetylene black, the binder sodium carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR) are mixed in a mass ratio of 77.6:19.4:1:1:1, in the preparation of the electrolyte, the relevant parameters are adjusted according to Table 1, and in the preparation of the lithium ion battery, the injection coefficient is adjusted to 1.7g / Ah, the rest is the same as in Example 1-1. Among them, M in the electrolyte A 、M B 、M C When the value of changes, the mass percentage of the solvent M F As a result, the mass percentage of the electrolyte M E Unchanged; Based on the mass of the negative electrode active material, the mass percentage of silicon element M Si is 20%.
[0097] Example 1-31 to Example 1-45
[0098] Except that in the preparation of the negative electrode sheet, the negative electrode active material artificial graphite, the negative electrode active material single substance silicon, the conductive agent acetylene black, the binder sodium carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR) are mixed in a mass ratio of 67.9:29.1:1:1:1, in the preparation of the electrolyte, the relevant parameters are adjusted according to Table 1, and in the preparation of the lithium ion battery, the injection coefficient is adjusted to 1.8g / Ah, the rest is the same as in Example 1-1. Among them, M in the electrolyte A 、M B 、M C When the value of changes, the mass percentage of the solvent M F As a result, the mass percentage of the electrolyte M E Unchanged; Based on the mass of the negative electrode active material, the mass percentage of silicon element M Si It is 30%.
[0099] Example 2-1 to Example 2-3
[0100] Except that the type of the compound shown in Formula 1 is adjusted according to Table 2 in <Preparation of Electrolyte>, the rest is the same as Example 1-1.
[0101] Example 2-4 to Example 2-8
[0102] Except that in the preparation of electrolyte, other additives are introduced into the electrolyte according to Table 2 and the content and type of other additives are adjusted, the rest is the same as Example 1-1. D When the mass percentage of the solvent M changes F The mass percentage of other components in the electrolyte remains unchanged. In Table 2, vinylene carbonate is abbreviated as VC and lithium bis(oxalatoborate) is abbreviated as LiBOB.
[0103] Embodiment 2-9
[0104] Except that in <Preparation of Electrolyte>, the electrolyte is adjusted to lithium hexafluorophosphate (LiPF6) and lithium bis(fluorosulfonyl)imide (LiFSI), and based on the mass of the electrolyte, the mass percentage of LiPF6 is 10% and the mass percentage of LiFSI is 5%, the rest is the same as Example 1-1.
[0105] Comparative Examples 1 to 6
[0106] Except that the relevant parameters in <Preparation of Electrolyte> are adjusted according to Table 1, the rest are the same as Example 1-1. A 、M B 、M C When the value of changes, the mass percentage of the solvent M FAs a result, the mass percentage of the electrolyte M E constant.
[0107] Comparative Examples 7 to 12
[0108] Except that the relevant parameters in <Preparation of Electrolyte> are adjusted according to Table 1, the rest are the same as in Example 1-16. A 、M B 、M C When the value of changes, the mass percentage of the solvent M F As a result, the mass percentage of the electrolyte M E constant.
[0109] Comparative Examples 13 to 18
[0110] Except that the relevant parameters in <Preparation of Electrolyte> are adjusted according to Table 1, the rest are the same as in Example 1-31. A 、M B 、M C When the value of changes, the mass percentage of the solvent M F As a result, the mass percentage of the electrolyte M E constant.
[0111] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Tables 1 and 2.
[0112] Table 1
[0113]
[0114] Note: “ / ” in Table 1 indicates no relevant preparation parameters.
[0115] From Example 1-1 to Example 1-45, Comparative Example 1 to Comparative Example 18, it can be seen that the electrolyte includes the compound shown in Formula 1 within the scope of the present application, fluoroethylene carbonate and difluorobis(oxalate) lithium phosphate, which can make the secondary battery have a higher 45°C capacity retention rate, a higher capacity recovery rate, a higher storage capacity retention rate, a lower thickness expansion rate and a lower impedance growth rate, indicating that the secondary battery has good high-temperature cycle performance, high-temperature storage performance and a lower impedance growth rate. However, Comparative Examples 1 to Comparative Examples 18 do not meet the above characteristics at the same time, and the secondary battery has a lower 45°C capacity retention rate, a lower capacity recovery rate, a lower storage capacity retention rate, a higher thickness expansion rate and a higher impedance growth rate, indicating that the high-temperature cycle performance and high-temperature storage performance of the secondary battery are poor, and the impedance growth rate is large.
[0116] M A 、M B 、MC 、M a 、M b 、M c 、M Si The relationship between M and will affect the high temperature cycle performance, high temperature storage performance and impedance growth rate of the secondary battery. A 、M B 、M C 、M a 、M b 、M c 、M Si The relationship between satisfies equation I, and the obtained secondary battery has a higher 45°C capacity retention rate, a higher capacity recovery rate, a higher storage capacity retention rate, a lower thickness expansion rate and a lower impedance growth rate, indicating that the secondary battery has good high-temperature cycle performance, high-temperature storage performance and a lower impedance growth rate.
[0117] M Si The value of M usually affects the high temperature cycle performance, high temperature storage performance and impedance growth rate of the secondary battery. Si The value is within the scope of the present application, and the obtained secondary battery has a higher 45°C capacity retention rate, a higher capacity recovery rate, a higher storage capacity retention rate, a lower thickness expansion rate and a lower impedance growth rate, indicating that the secondary battery has good high-temperature cycle performance, high-temperature storage performance and a lower impedance growth rate, while also taking into account the energy density of the secondary battery.
[0118] M a 、M b 、M c The value of M usually affects the high temperature cycle performance, high temperature storage performance and impedance growth rate of the secondary battery. From Example 1-1 to Example 1-45 and Comparative Example 1 to Comparative Example 18, it can be seen that by adjusting M a 、M b 、M c The value of is within the scope of the present application, and the obtained secondary battery has a higher 45°C capacity retention rate, a higher capacity recovery rate, a higher storage capacity retention rate, a lower thickness expansion rate and a lower impedance growth rate, indicating that the secondary battery has good high-temperature cycle performance, high-temperature storage performance and a lower impedance growth rate.
[0119] Table 2
[0120]
[0121] Note: “ / ” in Table 2 indicates no relevant preparation parameters.
[0122] The type of compound represented by Formula 1 usually affects the high temperature cycle performance, high temperature storage performance and impedance growth rate of the secondary battery. It can be seen from Example 1-1, Example 2-1 to Example 2-3, and Comparative Example 1 that when the electrolyte includes the compound represented by Formula 1 within the scope of the present application, the obtained secondary battery has a higher 45°C capacity retention rate, a higher capacity recovery rate, a higher storage capacity retention rate, a lower thickness expansion rate and a lower impedance growth rate, indicating that the secondary battery has better high temperature cycle performance, high temperature storage performance and a lower impedance growth rate.
[0123] Types and mass percentage of other additives M D It usually affects the high-temperature cycle performance, high-temperature storage performance and impedance growth rate of the secondary battery. It can be seen from Example 1-1, Example 2-4 to Example 2-8 that when the electrolyte includes other additives within the scope of this application and regulates other additives within the scope of this application, the obtained secondary battery has a higher 45°C capacity retention rate, a higher capacity recovery rate, a higher storage capacity retention rate, a lower thickness expansion rate and a lower impedance growth rate, indicating that the secondary battery has better high-temperature cycle performance, high-temperature storage performance and a lower impedance growth rate.
[0124] Type and mass percentage of electrolyte M E It usually affects the high temperature cycle performance, high temperature storage performance and impedance growth rate of the secondary battery. It can be seen from Examples 1-1 and 2-9 that when the electrolyte includes an electrolyte within the scope of this application and the mass percentage of the electrolyte is regulated within the scope of this application, the obtained secondary battery has a higher 45°C capacity retention rate, a higher capacity recovery rate, a higher storage capacity retention rate, a lower thickness expansion rate and a lower impedance growth rate, indicating that the secondary battery has good high temperature cycle performance, high temperature storage performance and a lower impedance growth rate.
[0125] Type and mass percentage of solvent M F It usually affects the high temperature cycle performance, high temperature storage performance and impedance growth rate of the secondary battery. It can be seen from Example 1-1, Example 2-1 to Example 2-9 that when the electrolyte includes a solvent within the scope of this application and the mass percentage of the solvent is regulated within the scope of this application, the obtained secondary battery has a higher 45°C capacity retention rate, a higher capacity recovery rate, a higher storage capacity retention rate, a lower thickness expansion rate and a lower impedance growth rate, indicating that the secondary battery has good high temperature cycle performance, high temperature storage performance and a lower impedance growth rate.
[0126] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A secondary battery comprising a negative electrode sheet, a positive electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet comprises a negative electrode material layer, the negative electrode material layer comprises a negative electrode active material, and the mass percentage of silicon element is M based on the mass of the negative electrode active material. Si , which satisfies 10%≤M Si ≤30%; the electrolyte comprises a solvent, an electrolyte and an additive, and the additive comprises a compound represented by Formula 1, fluoroethylene carbonate and lithium difluorobis(oxalate)phosphate; Formula 1, Based on the mass of the electrolyte, the mass percentage of the compound represented by Formula 1 is M A The mass percentage of the fluoroethylene carbonate is M B The mass percentage of the lithium difluorobis(oxalate)phosphate is M C , meet: 0.5%≤M A ≤7%, 5%≤M B ≤20%, 0.1%≤M C ≤1%; After the secondary battery is formed, based on the mass of the electrolyte, the mass percentage of the compound represented by Formula 1 is M a The mass percentage of the fluoroethylene carbonate is M b The mass percentage of the lithium difluorobis(oxalate)phosphate is M c ; The formation condition is to place the secondary battery in an environment of 40°C to 50°C, charge it with a constant current, charge the secondary battery to a charge state of 70% to 100%, and the constant current is 0.05C to 0.15C; The secondary battery satisfies the relational formula I: 15≤[15×(M A +M B ) / (M a +M b )+10×M C ×(M C -M c )] / (1.5+M Si )≤234, where The injection coefficient of the secondary battery is 1.5+M Si , unit is g / Ah; The secondary battery meets the following conditions: (1)0.01%≤M a ≤1.81%; (2)0.24%≤M b ≤7.23%; (3)0%≤M c ≤0.33%。 2. The secondary battery according to claim 1, which satisfies at least one of the following conditions: (1) 1% ≤ M A ≤5%; (2) 10% ≤ M B ≤15%; (3) 0.5%≤M C ≤1%.
3. The secondary battery according to claim 1 or 2, wherein: The additives also include other additives, and the other additives are selected from at least one of vinylene carbonate and lithium bis(oxalatoborate); based on the mass of the electrolyte, the mass percentage of the other additives is M D , 0.3%≤M D ≤5%.
4. The secondary battery according to claim 1 or 2, wherein the electrolyte is selected from at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalatoborate) and lithium difluorooxalatoborate, and the mass percentage of the electrolyte is M based on the mass of the electrolyte. E , 12%≤M E ≤18%; The solvent is selected from at least two of propylene carbonate, ethyl methyl carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, cyclopentane, methyl formate, ethyl formate, propyl formate, butyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate and butyl butyrate, and the mass percentage of the solvent based on the mass of the electrolyte is M F , 55%≤M F ≤80%.
5. The secondary battery according to claim 1, wherein the secondary battery satisfies the relation II: 16≤[15×(M A +M B ) / (M a +M b )+10×M C ×(M C -M c )] / (1.5+M Si )≤83.
3.
6. The secondary battery according to claim 5, wherein the secondary battery satisfies the relational formula III: 16≤[15×(M A +M B ) / (M a +M b )+10×M C ×(M C -M c )] / (1.5+M Si )≤33.
